Flexible Photocatalytic Paper with Cu2O and Ag Nanoparticle-Decorated ZnO Nanorods for Visible Light Photodegradation of Organic Dye - Cheng-En Tsai; Shang-Ming Yeh; Chien-Hua Chen; Heh-Nan Lin (Nanoscale Research Letters, 2019)
Abstract We report on the fabrication of flexible photocatalytic paper comprised of Cu2O and Ag nanoparticle (NP)-decorated ZnO nanorods (NRs) and its application in visible light photodegradation of organic dye. ZnO NRs are first grown on a kraft paper substrate using a hydrothermal method. The NRs are subsequently decorated with Cu2O, Ag, or both NPs formed by photoreduction processes. Scanning electron microscopy and X-ray diffraction analysis confirm the crystallinity of ZnO NRs. Transmission electron microscopy analysis confirms the compositions of the two types of NPs. Four different types of photocatalytic papers with a size of 10 × 10 cm2 are prepared and used to degrade a 10-μM and 100-mL rhodamine B solution. The paper with Cu2O and Ag NP-co-decorated ZnO NRs has the best efficiency with first-order kinetic constants of 0.017 and 0.041 min−1 under the illumination of a halogen lamp and direct sunlight, respectively. The performance of the photocatalytic paper compares well with other substrate-supported ZnO nanocomposite photocatalysts. With the advantages of flexibility, light weight, nontoxicity, low cost, and ease of fabrication, the photocatalytic paper has good potential for visible light photocatalysis.